DYSTOCIA DUE TO FETAL ANASARCA IN A CROSS-BRED COW - GHUMAN, S P S; HONPARKHE, M; SINGH, JAGIR (The Indian Journal of Animal Reproduction, 2011)
A case of dystocia due to an unusually observed neck-brisket edema in an anasarcic fetus of a cross-bredcow and its vaginal delivery is reported.
Keywords: Brisket edema; Cow; Fetal anasarca; Vaginal delivery